Gambaran pengetahuan dan sikap guru SDN 1 Malalayang Kota Manado mengenai kekerasan pada anak - Husa, Rahdian; Palandeng, Henry M. F.; Ratag, Gustaf A. E. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Objective: The purpose of this study is to describe the knowledge and attitudes of elementary school teachers toward the child abuse Design: This research is a qualitative descriptive study with a grounded theory approach using the technique of focus group discussions and in-depth interviews. The location of studywas at SDN (Elementary School) 1 Malalayang, City of Manado Result: Results showed, in general informants know the definition, type, effects, signs and prevention of child abuse. Resources informant comes mostly from education and experience as a teacher. Conclusion. Teachers are inadequatly knowing some aspects of child abuse. The teacher’s attitude focused on prevention, and tend to report cases of child abuse in certain condition. Keywords: Teacher’s knowledge, teacher’s attitude, child abuse